Major Problems Associated with Rules on Permanent Establishment under Ethiopian Income Tax Law - Adugna, Alemu (Bahir Dar University Journal of Law, 2023)
The allocation of taxing rights between the states with respect of businessprofits is a very complex activity. The central notion of the allocationrules is the Permanent Establishment (PE). However, owing to the gapsor mismatches that attributed to the definition of PE as envisaged undertax treaties and national laws, base erosion and profit shifting became aninternational agenda. This article examines the concept of PE as definedunder the Ethiopian income tax law, identifies its shortcomings andexplores opportunities for proper regulation. To this end, it employeddoctrinal legal research method to investigate the pertinent provision ofincome tax law. Accordingly, the finding of the paper shows severalpitfalls of Ethiopian income tax regime concerning permanentestablishment. Absence of definition for the elements of a permanentestablishment, total disregard of permanent establishment concerning ECommerce, and its failure to manage artificial avoidance of permanentestablishment status are among the major problems. Furthermore,absence of any clarification concerning a place of management andeffective place of management, which is provided as a requirement fordetermining whether a foreign enterprise has a permanent establishmentor a resident respectively, and absence of exceptions for the interruptionof activities via force majeure in relation to construction or building andservice permanent establishment are other problems of Ethiopian incometax law. Accordingly, multinational corporations may resort to baseerosion and profit shifting by using the gaps that are left by Ethiopian taxregime. Hence, Ethiopian income tax law should be amended in a waythat solves the aforementioned lacunas.